The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jfpp.15028
|View full text |Cite
|
Sign up to set email alerts
|

Development of halal cooked smoked beef and turkey sausage using a combined plant extracts

Abstract: The relevance of the study is due to the fact that in recent years the demand for meat products has increased, which in turn makes it necessary to improve the quality of products, due to plant extracts. With the use of low‐frequency vacuum ultrasonic technology, the combined extract of local plant materials—hawthorn, sage, thyme, oregano, basil, and cloves—enriches the organoleptic properties and nutritional value. The purpose of the study was to develop a new technology of cooked smoked beef and turkey sausag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Морфологиялық құрамы жағынан етбұлшықет пен дәнекер тіндердің қосындысы [9,10,11]. Тарылудың құрылымы мен сипатына қарай бұлшықет тіні жолақты, жүрек және тегіс бұлшықеттерге бөлінеді.…”
Section: нәтижелер және оларды талқылауunclassified
“…Морфологиялық құрамы жағынан етбұлшықет пен дәнекер тіндердің қосындысы [9,10,11]. Тарылудың құрылымы мен сипатына қарай бұлшықет тіні жолақты, жүрек және тегіс бұлшықеттерге бөлінеді.…”
Section: нәтижелер және оларды талқылауunclassified
“…that it contains (in mg/100 g) minerals that were absent in the undiluted drink: magnesium -1.12; copper -0.044; vitamins: pantothenic acid -0.437; nicotinic acid -0.203; riboflavin -0.033; vitamin E -2. 16…”
Section: The Objects Of the Study Are A Fermented Milk Product Made O...mentioning
confidence: 99%
“…Therefore, it is necessary to choose a method for extracting the necessary nutrients from them. To isolate these substances from the seeds in question, it is of interest to choose the extraction method [16].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…1–3 log cycle reduction of S. typhimurium and S. aureus (Jattar‐Santiago et al, 2022). Zheleuova et al (2021) developed halal‐cooked smoked beef and turkey meat products by using a combination of plant extract viz., hawthorn, sage, thyme, oregano, basil, and cloves. Authors reported changes in sensory attributes mainly taste and smell.…”
Section: Commonly Used Plant Extracts In Meatmentioning
confidence: 99%